Platinum dissolution and tissue response following long-term electrical stimulation at high charge densities. (17th March 2021) - Shepherd, Robert K; Carter, Paul M; Dalrymple, Ashley N; Enke, Ya Lang; Wise, Andrew K; Nguyen, Trung; Firth, James; Thompson, Alex; Fallon, James B
Abstract: Objective . Established guidelines for safe levels of electrical stimulation for neural prostheses are based on a limited range of the stimulus parameters used clinically. Recent studies have reported particulate platinum (Pt) associated with long-term clinical use of these devices, highlighting the need for more carefully defined safety limits. We previously reported no adverse effects of Pt corrosion products in the cochleae of guinea pigs following 4 weeks of electrical stimulation using charge densities far greater than the published safe limits for cochlear implants. The present study examines the histopathological effects of Pt within the cochlea following continuous stimulation at a charge density well above the defined safe limits for periods up to 6 months. Approach . Six cats were bilaterally implanted with Pt electrode arrays and unilaterally stimulated using charge balanced current pulses at a charge density of 267 μ C cm −2 phase −1 using a tripolar electrode configuration. Electrochemical measurements were made throughout the implant duration and evoked potentials recorded at the outset and on completion of the stimulation program. Cochleae were examined histologically for particulate Pt, tissue response, and auditory nerve survival; electrodes were examined for surface corrosion; and cochlea, brain, kidney, and liver tissue analysed for trace levels of Pt. Main results . Chronic stimulation resulted in both a significant increase in tissue response and particulate Pt within the tissue capsule surrounding the electrode array compared with implanted, unstimulated control cochleae. Importantly, there was no stimulus-induced loss of auditory neurons (ANs) or increase in evoked potential thresholds. Stimulated electrodes were significantly more corroded compared with unstimulated electrodes. Trace analysis revealed Pt in both stimulated and control cochleae although significantly greater levels were detected within stimulated cochleae. There was no evidence of Pt in brain or liver; however, trace levels of Pt were recorded in the kidneys of two animals. Finally, increased charge storage capacity and charge injection limit reflected the more extensive electrode corrosion associated with stimulated electrodes. Significance . Long-term electrical stimulation of Pt electrodes at a charge density well above existing safety limits and nearly an order of magnitude higher than levels used clinically, does not adversely affect the AN population or reduce neural function, despite a stimulus-induced tissue response and the accumulation of Pt corrosion product. The mechanism resulting in Pt within the unstimulated cochlea is unclear, while the level of Pt observed systemically following stimulation at these very high charge densities does not appear to be of clinical significance.